1998
DOI: 10.1111/j.1600-079x.1998.tb00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the subcellular distribution of calmodulin by melatonin in MDCK cells

Abstract: In this paper we describe the interaction of melatonin with calmodulin in MDCK cells. The double staining immunofluorescent method showed that calmodulin in control MDCK cells appeared as fluorescent spots at the cell periphery. In contrast, MDCK cells cultured with 10(-9) M melatonin for 6, 12, 24 hr or for 4 days showed that calmodulin fluorescent spots were distributed throughout the cytoplasm as well as in the nucleus. These calmodulin rearrangements were reversed 6 hr after melatonin withdrawal. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
(6 reference statements)
1
20
0
Order By: Relevance
“…Similar effects are obtained with the CaM antagonists trifluoperazine (10 μ M) and compound 48/80 (30 μ g/mL) [32]. The CaM antagonism by melatonin is supported by the fact that the indole binds with high affinity (180 pM) to purified liposome‐incorporated CaM [34] as well as to membrane‐bound [35] and cytoplasmic CaM [36], and because in vitro this indole inhibits the activity of CaM‐dependent enzymes such as cAMP phosphodiesterase [37], nitric oxide synthase [38] and CaM‐kinase II [39]. Direct interaction of melatonin with intact calcium‐saturated CaM has also been recently studied by fluorescence and nuclear magnetic resonance spectroscopies [40].…”
Section: Melatonin and The Cytoskeletonmentioning
confidence: 57%
“…Similar effects are obtained with the CaM antagonists trifluoperazine (10 μ M) and compound 48/80 (30 μ g/mL) [32]. The CaM antagonism by melatonin is supported by the fact that the indole binds with high affinity (180 pM) to purified liposome‐incorporated CaM [34] as well as to membrane‐bound [35] and cytoplasmic CaM [36], and because in vitro this indole inhibits the activity of CaM‐dependent enzymes such as cAMP phosphodiesterase [37], nitric oxide synthase [38] and CaM‐kinase II [39]. Direct interaction of melatonin with intact calcium‐saturated CaM has also been recently studied by fluorescence and nuclear magnetic resonance spectroscopies [40].…”
Section: Melatonin and The Cytoskeletonmentioning
confidence: 57%
“…Further, melatonin has been shown to reduce oxidative stress-induced post-ischemic myocardial recovery, protect against ischemia reperfusion injury, reduce cardiac arrhythmia, and protect against various other forms of cardiovascular abnormalities [12][13][14][15][16]. In addition to being an effective free radical scavenger, melatonin also enhances the activity of the membrane calcium pump [17] that regulates calmodulin [18] and decreases the intracellular calcium concentration [19]. Moreover, melatonin has been reported in several dietary plants and as a phytochemical in olive oil and, recently, it has been suggested that melatonin present in edible plants may improve human health by virtue of its biological activities and good bioavailability [20].…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, an earlier study reported that melatonin at a physiological concentration (1 n m ) modulated the subcellular localization of calmodulin in MDCK cells . Whether pharmacological levels of melatonin affect the intracellular position of calmodulin remains to be determined.…”
Section: Melatonin As a Conditional Pro‐oxidantmentioning
confidence: 99%